Kościół ewangelicki przyczółkiem opozycji wschodnioniemeickiej - Michalak, Jakub (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Evangelical Church had an important role in the GDR as far as the activities of opposition at the beginning of 1970s and 1980s are concerned. Indeed, it was outside the institution of the Unity Party. Within the vicinity of the church, people were to create a feeling of solidarity between those aggrieved by the system and the first grassroots activists. During 1989 and 1990 Lutheran church became the starting point for mass demonstrations and a peaceful revolution. In addition, the invitation of the party and the opposition to committees’ meeting on Dec. 7, 1989 was published on behalf of the Association of Evangelical Churches.